Detecção de genes diferencialmente expressos na formiga urbana Camponotus vittatus (Hymenoptera, Formicinae) - Rodovalho, Cynara de Melo (2006)
Social insects inspire great curiosity, interest and a wish to know the social life molecular basis. Differentially expressed genes identification has been used with the objective to understand either the gene function and the molecular mechanisms of different biological processes. In this study, two protocols for the total RNA extraction from Camponotus vittatus were tested and the Differential Display Reverse Transcriptase Polymerase Chain Reaction (DDRT-PCR) technique was used with the aim to identify differentially expressed genes in caste, sex and development stages of this ant. The RNA extraction method, based in Chomczynski e Sacchi (1987), was the most efficacious. The DDRT-PCR technique was efficient for the detection of differentially expressed genes from C. vittatus. Three expressed sequence tags (ESTs) were sequenced and the analysis with bioinformatics tools failed in detect similarity with those sequences from data banks. These sequences may be new and, perhaps, specific of C. vittatus. They were deposited in dbEST database. A differentially expressed fragment, specific of works, was obtained with the primers HT11G and AP03. The results of its sequence and the analysis by bioinformatics revealed that this EST was, in fact, been isolated from the endosymbiotic bacteria of C. vittatus because a grol domain was detected and was observed high similarity with many proteins of the chaperonin family, a kind of protein present in the endosymbiotic bacterias of this genus.